The prediction of morbidity related to vaginal delivery in nulliparous women – A secondary analysis from the genesis multicenter trial. (September 2021) - Ismail, Khadijah I.; Burke, Naomi; Burke, Gerard; Breathnach, Fionnuala; McAuliffe, Fionnuala M.; Morrison, John J.; Turner, Michael J.; Dornan, Samina; Higgins, John R.; Cotter, Amanda; Geary, Michael; McParland, Peter; et al.
Highlights: A trend toward increasing morbidity was observed with increasing Genesis risk score. A trend toward increasing rate of operative vaginal delivery was also observed. The Genesis nomogram has the potential to estimate maternal and neonatal morbidity. Abstract: Objective: In the prospective multicenter Genesis study, we developed a prediction model for Cesarean delivery (CD) in term nulliparous women. The objective of this secondary analysis was to determine whether the Genesis model has the potential to predict maternal and neonatal morbidity associated with vaginal delivery. Study design: The national prospective Genesis trial recruited 2, 336 nulliparous women with a vertex presentation between 39 + 0- and 40 + 6-weeks' gestation from seven tertiary centers. The prediction model used five parameters to assess the risk of CD: maternal age, maternal height, body mass index, fetal head circumference and fetal abdominal circumference. Simple and multiple logistic regression analyses were used to develop the Genesis model. The risk score calculated using this model were correlated with maternal and neonatal morbidity in women who delivered vaginally: postpartum hemorrhage (PPH), obstetric anal sphincter injury (OASI), shoulder dystocia, one- and five-minute Apgar score ≤ 7, neonatal intensive care (NICU) admission, cephalohematoma, fetal laceration, nerve palsy and fractures. The morbidities associated with spontaneous vaginal delivery were compared with those associated with operative vaginal delivery (OVD). The likelihood ratios for composite morbidity and the morbidity associated with OVD based on the Genesis risk scores were also calculated. Results: A total of 1, 845 (79%) nulliparous women had a vaginal delivery. A trend of increasing intervention and morbidity was observed with increasing Genesis risk score, including OVD (p < 0.001), PPH (p < 0.008), NICU admission (p < 0.001), low Apgar score at one-minute (p < 0.001) and OASI (p = 0.009). The morbidity associated with OVD was significantly higher compared to spontaneous vaginal delivery, including NICU admission (p < 0.001), PPH (p = 0.022), birth injury (p < 0.001), shoulder dystocia (p = 0.002) and Apgar score of<7 at one-minute (p < 0.001). The positive likelihood ratios for composite outcomes (where the OVD was excluded) increases with increasing risk score from 1.005 at risk score of 5% to 2.507 for risk score of>50%. Conclusion: In women who ultimately achieved a vaginal birth, we have shown more maternal and neonatal morbidity in the setting of a Genesis nomogram-determined high-risk score for intrapartum CD. Therefore, the Genesis prediction tool also has the potential to predict a more morbid vaginal delivery.